Off-Target Influences of Arch-Mediated Axon Terminal Inhibition on Network Activity and Behavior - Lafferty, Christopher K.; Britt, Jonathan P. (Frontiers in Neural Circuits, 2020)
Archaerhodopsin (ArchT)-mediated photoinhibition of axon terminals is commonly used to test the involvement of specific long-range neural projections in behavior. Although sustained activation of this opsin in axon terminals has the unintended consequence of enhancing spontaneous vesicle release, it is unclear whether this desynchronized signaling is consequential for ArchT’s behavioral effects. Here, we compare axon terminal and cell body photoinhibition of nucleus accumbens (NAc) afferents to test the utility of these approaches for uncovering pathway-specific contributions of neural circuits to behavior. First, in brain slice recordings we confirmed that ArchT photoinhibition of glutamatergic axons reduces evoked synaptic currents and increases spontaneous transmitter release. A further consequence was increased interneuron activity, which served to broadly suppress glutamate input via presynaptic GABAB receptors. In vivo, axon terminal photoinhibition increased feeding and reward-seeking behavior irrespective of the afferent pathway targeted. These behavioral effects are comparable to those obtained with broad inhibition of NAc neurons. In contrast, cell body inhibition of excitatory NAc afferents revealed a pathway-specific contribution of thalamic input to feeding behavior and amygdala input to reward-seeking under extinction conditions. These findings underscore the off-target behavioral consequences of ArchT-mediated axon terminal inhibition while highlighting cell body inhibition as a valuable alternative for pathway-specific optogenetic silencing.